Taking Music To The Streets : Busking, The New Pop Culture - Parveen, Kaur (Publications International, 2018)
Buskers are not valued highly in Malaysia because they are viewed as obstructions of public space. This study is an attempt to understand buskers and their culture to bridge the gap of knowledge in society. This study aims to explore how busking is socially and culturally constructed, and critically evaluate social power imposed over them. Buskers are being restricted from voicing out their expression of art as they are often associated with adjectives such as ‘violent, rebellious, lazy, and unemployed'. In this research, a qualitative analysis through in-depth interviews and participant observation were conducted on buskers in Kuching. There are several factors that motivate them to busk. These factors can be divided into intrinsic and extrinsic factors. Intrinsic motivation is seen to be the inherent tendency to seek out challenges to constantly dare one's capabilities and learn new things. In contrast, extrinsic factors come from social pressures to do something that would allow one to partake in a certain kind of responsibility. Even though busking is generally an enjoyable activity meant to provide pleasure to the public, at times the buskers face certain challenges from the society. The social construction of the society towards buskers as a bad role model has led authority figures to enforce certain policies to control them.